English as a Medium of Instruction in Asia: Examining Roles, Opportunities and Challenges, and Effective Practices - Saldo, Joyline; Atonen, Ayrah Mae; Ben-at, Nicole; Sagang, Aira Jonah; Pelila, John Rey (Papanda Publisher, 2025)
Research shows that English as a Medium of Instruction (EMI) significantly impacts higher education globally; however, more studies on its implementation in specific regions, particularly in Asia, are needed. This review examines how EMI is used in Asia by analyzing 30 peer-reviewed articles published between 2020 and 2024 from the ERIC and Taylor and Francis database. The findings highlight that EMI improves language skills, academic literacy, global competitiveness, and cultural awareness. However, its success depends on several factors, such as adapting teaching strategies, providing institutional support, and using approaches like translanguaging to overcome language barriers and meet diverse student needs. While EMI offers benefits like enhanced language proficiency, confidence, teamwork, and career readiness, it also faces challenges, including limited English proficiency, insufficient teacher training, lack of support, cultural concerns, and increased student pressure. To address these challenges and improve EMI outcomes, educators are encouraged to use interactive teaching methods, refine assessment practices, and foster cross-cultural understanding. Institutions should also focus on strengthening teacher training, improving language support, and enhancing course quality, while students are urged to build confidence and critical thinking skills. In conclusion, while EMI is a valuable tool for advancing education in Asia, its success depends on careful planning, strong support systems, and flexible teaching strategies.